Exposure to high-altitude hypobaric hypoxic environment induces low-frequency hearing loss in C57BL/6J mice: Mediated by slowing down the postsynaptic electrical signal transmission speed in the cochlear-inferior colliculus auditory signaling pathway - Benhong Ren; Qingping Zhang; Wenyuan Gan; Guanghao Yue; Shanhong Li; Xiaoli Zhang; Wenjun Cao; Feng Tang; Ying Zhang; Bin Guo; Yi Wang (PLoS ONE, 2026)
Objective To reveal the pattern of effects of exposure to high-altitude hypobaric hypoxia environment on the auditory function of C57BL/6J mice, so as to provide a theoretical basis for the targeted prevention and treatment of hearing loss, tinnitus, and otogenic vertigo in high-altitude areas. Methods Forty male C57BL/6J mice were randomly divided into a control group and an experimental group. The experimental group was further subdivided into 9 subgroups according to the exposure duration (3, 5, 7, 10, 15, 20, 25, 30, and 35 days), with 4 mice in each subgroup. Mice in the experimental group were housed in a hypobaric hypoxic chamber simulating an altitude of 6000 meters. Auditory function-related indicators of mice in both groups were detected using auditory brainstem response (ABR), electrocochleography (ECochG), and distortion product otoacoustic emissions (DPOAE). Statistical methods were used to compare the intergroup differences. Results Results of ABR testing: Under click stimulation, the latencies of Waves I, II, III, IV, and V, as well as the I-III interwave interval, were significantly prolonged in all subgroups of the experimental group. Abnormal changes (elevation or reduction) in the amplitudes of Waves II and III were observed, and hearing thresholds were significantly elevated ( P < 0.05). Under stimulation with low-frequency 4000 Hz and 8000 Hz pure tones, all subgroups of the experimental group also exhibited similar changes as mentioned above ( P < 0.05). Horizontal comparison of different stimulation conditions (click, 4000 Hz, 8000 Hz) within the experimental group revealed that the degree of hearing loss was more significant in the click group and 4000 Hz pure tone stimulation group than in the 8000 Hz group ( P < 0.05). Results of ECochG testing: The latencies of the summating potential (-SP) and compound action potential (AP) were generally prolonged in all subgroups of the experimental group. Among them, the -SP/AP amplitude ratio was > 0.4 in the subgroups exposed for 3, 5, 15, 20, 25, and 30 days ( P < 0.05), and the -SP/AP area ratio was > 2.0 in the 7-day exposure subgroup. Results of DPOAE testing: Among all 40 mice, only 3 passed the test, with a pass rate of 7.5%, and all of these 3 mice were from the control group. Conclusion Exposure to a high-altitude hypobaric hypoxia environment can induce low-frequency hearing loss in C57BL/6J mice, and the process of auditory response regulation and adaptation of mice to this environmental stimulus exhibits time dependence. Further analysis revealed that this low-frequency hearing loss is closely associated with the slowing of postsynaptic electrical signal transmission speed in the cochlea-inferior colliculus auditory conduction pathway; the mechanism underlying this slowing of electrical signal transmission may be related to changes in voltage or resistance at various sites of the auditory pathway during sound signal conduction. Based on auditory physiological mechanisms, it is hypothesized that the aforementioned abnormal changes in voltage or resistance may be associated with endolymphatic hydrops, suggesting that endolymphatic hydrops may be one of the potential key links through which the high-altitude hypobaric hypoxia environment affects auditory conduction function.